126 The impact of nice guidelines for the investigation of chest pain on outpatient cardiology services in the UK. (9th June 2011) - Patterson, C; Nicol, E; Bryan, L; Woodcock, T; Padley, S; Bell, D
Abstract : Introduction: The National Institute for Health and Clinical Excellence (NICE) have released guidelines for the investigation of chest pain of recent onset (1). There is concern that the guidelines will increase the burden on cardiac imaging, requiring service reconfiguration and investment (2, 3). This study was performed to assess the impact of the guidelines on outpatient cardiology services in the UK. Methods: 595 consecutive patients attending chest pain clinics at two hospitals over six months preceding release of the NICE guidelines (51% male; median age 55 yrs (range 22–94 yrs)) were risk stratified using NICE criteria. Preliminary cardiac investigations recommended by NICE were compared with existing clinical practice and the relative costs calculated. Results: NICE would have recommended 443 patients (74%) for discharge without cardiac investigation, 10 (2%) for cardiac computed tomography (CCT), 69 (12%) for functional cardiac imaging and 73 (12%) for invasive coronary angiography (ICA). Relative to existing practice there would have been a trend towards reduced functional cardiac imaging (−24%; p=0.06) and increased CCT (+43%; p=0.436) but a significant increase in ICA (+508%; p<0.001). The cost of investigations recommended by NICE would have been £15 881 greater than existing practice. Conclusions: This study suggests implementation of the NICE guidelines will require investment in cardiology services, particularly ICA. It will be necessary to establish and maintain CCT for relatively few patients; also to establish and maintain functional cardiac imaging even though referrals are likely to decline. Individual hospitals should assess their local populations prior to service reconfiguration.